Evaluation of Chicken Eggshell Biocoagulant Application in Domestic Wastewater Treatment - Dellarosa, Luvy; Andhini, Marliza; Ratnawati, Beata; Tunggadewi, Andini Tribuana; Pramitadevi, Yudith Vega; Suri, Wiranda Intan; Jannah, Nurul; Hidiya, Miesriany; Wahdi, Emil; Prasetya, Dimas Ardi; Saputra, Septian Fauzi Dwi; Budiharto, Ivone Wulandari (Riwayat: Educational Journal of History and Humanities, 2025)
The increasing population in Bogor City, especially in the Tanah Baru area, leads to an increase in the volume of domestic wastewater and municipal waste such as chicken eggshells. Chicken eggshells have the potential to be used as an environmentally friendly biocoagulant to reduce pollutant load, but their effectiveness on domestic wastewater still needs to be studied. This study aims to analyze the effect of adding chicken eggshell biocoagulant on changes in pH, TDS, and conductivity parameters of domestic wastewater and compare it with the conventional coagulant polyaluminum chloride (PAC). The methods used include preparing chicken eggshell powder through washing, drying, grinding, sieving, and chemical activation, then applying it to wastewater samples at a dosage of 50 g/500 mL and comparing it with PAC at a dosage of 1 mL/500 mL using the jar test. The results show that adding chicken eggshell biocoagulant did not significantly reduce pollutant load, even causing an increase in TDS and conductivity, while PAC was able to improve wastewater quality with much lower increases in TDS and conductivity, and the pH remained within the quality standard range. These findings indicate that chemically, chicken eggshells are more suitable for use as an adsorbent or support material in coagulation systems than as the primary coagulant in domestic wastewater treatment.